(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Shaivism refers to a religious tradition, which focuses on the deity Shiva. The worshippers of god Shiva are called Shaivas. Shaivism developed as a major system of religious beliefs and practices in India. It is very difficult to trace the early history of Shaivism. There are wide gaps in the available records, but we know that at each point where the veil of history lifts, the worship of Shiva was there. In the 7,000 years old Indus Valley Civilization, we find the famous seal of Shiva known as Lord Pashupati. The seal shows Shiva seated in a yogic pose.